2015
DOI: 10.21897/rmvz.76
|View full text |Cite
|
Sign up to set email alerts
|

Quality Index Method developed for gutted and ungutted red tilapia (Oreochromis ssp)

Abstract: Objective. To develop a Quality Index Method (QIM) for gutted and ungutted red tilapia from aquaculture ponds. Materials and methods. 40 specimens of gutted red tilapia and 40 ungutted ones were located in foam polyethylene boxes within layers of ice and storage at 4°C. Three fish were randomly sampled on days 0, 3,5,8,11,14 and 17 for gutted tilapia, and on days 0, 3, 6, 9, 11, 14 and 16 for ungutted tilapia. A sensorial panel of 8 experts was formed to evaluate the product. With three samples each day with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[16] A total of 16 demerit points were determined in fresh whole harvested tilapia (O. shiranus), [22] 20 for bogue (B. boops) that were caught from the beneath of the fish farm from the natural environment, [17] 23 for anchovy, [19] and 23 for gutted Acoupa weak fish (C. acoupa) that were stored in ice. [23] Similarly, 29 and 21 demerit points were observed in whole and gutted red tilapia (Oreochromis ssp), [21] respectively, 28 for anchovy (E. anchoita) in ice, [18] 20 for sardines (S. pilchardus) in ice, [20] and 30 for fresh whole P. bogaraveo. [24] Compared to our study in whole and gutted rainbow trout, reported higher demerit points were reported for rainbow trout, [32] in flounder (P. patagonicus), [25] and Andrade et al [26] 33 demerit points for mullet (M. platanus).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[16] A total of 16 demerit points were determined in fresh whole harvested tilapia (O. shiranus), [22] 20 for bogue (B. boops) that were caught from the beneath of the fish farm from the natural environment, [17] 23 for anchovy, [19] and 23 for gutted Acoupa weak fish (C. acoupa) that were stored in ice. [23] Similarly, 29 and 21 demerit points were observed in whole and gutted red tilapia (Oreochromis ssp), [21] respectively, 28 for anchovy (E. anchoita) in ice, [18] 20 for sardines (S. pilchardus) in ice, [20] and 30 for fresh whole P. bogaraveo. [24] Compared to our study in whole and gutted rainbow trout, reported higher demerit points were reported for rainbow trout, [32] in flounder (P. patagonicus), [25] and Andrade et al [26] 33 demerit points for mullet (M. platanus).…”
Section: Discussionmentioning
confidence: 91%
“…Massa et al [18] indicated the shelf life of anchovy (E. anchoita) as 7 days while Pons-Sanchez-Cascado et al [19] reported 5 days shelf life for anchovy (E. encrasicholus). Another study [21] reported the shelf life of whole and gutted red tilapia (Oreochromis spp) as 6-9 and 8-11 days, respectively. For gutted Acoupa weakfish (C. acoupa) the shelf life was determined as 8-9 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer the fish is kept in the ice, the more microbiological and physicochemical processes occur, altering the fish in ways that are immediately perceptible to the senses. For instance, red tilapia scored 21 points after 17 days (Gutiérrez et al, 2015), but ungutted red tilapia scored 29 points after 16 days. Fish hardness is measured by pressing down on a muscle with your finger and seeing how quickly it springs back to its original shape.…”
Section: Oladeinde Et Al 2022 Ojas 3(1) | 0mentioning
confidence: 99%